PARADIGMA KARBALA DAN PROTES POLITIK KAUM SYI`AH * - Ihsan Ali Fauzi (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2016)
The Martyrdom of Husein in Karbala became cultural power for Syiah followers from any political and social groups, to protest what they considered as inequity. Why the Martyrdom of Husein was so important for Syiah followers? What is moral message behind his martyrdom so that it has been keeping and even developing until now? Some of modern Syiah followers utilize to protest against inequity. On the contrary, the opponents of Syiah also utilize the event for the opposite objectives. This article investigates why the martyrdom of Husain in Karbala so important and addresses the cultural and political effects of Karbala event from historical perspective.